Determination of fipronil insecticide and its sulfone metabolite in internal organs of white albino rats - Mohamed Mohamed Salim, Yehia (International Journal of Pharmacology and Toxicology, 2020)
Fipronil is a popular insecticide against a wide range of household, urban, agricultural, animal pests. It gets converted into several metabolites in animals and humans but mainly to fipronil sulfone, which is more toxic and persistent. Therefore, the current study aimed to investigate the presence of fipronil and fipronil sulfone in tissues of internal organs of white albino rats using gas chromatography coupled with mass spectroscopy (GC-MS) after oral administration of rats of repetitive sublethal doses of fipronil for 14 days. Results showed that the R2 values of standard curves of detected compounds were 0.9871 and 0.9989 for FIP and fipronil sulfone, respectively with LOQ of fipronil and fipronil sulfone of 5 and 10 µg/g. Average recovery percentages were from 96.3±5.4 to 101±8.5% and 93.8±4.7 to 98.4±5.1% for fipronil and fipronil sulfone, respectively with RSD values lower than 10%. Fipronil was detected in all tested organs. It was concentrated with great amounts in the lungs, liver, and kidney followed by testes, spleen, and brain, while fipronil sulfone was detected in the liver, testes, spleen, and lungs tissues in descending order. Fipronil was biotransformed into fipronil sulfone at different organs of white albino rats and the GC-MS coupled with the QuEChERS extraction and clean-up method were efficient in detecting them in the internal organs of rats.